Trauma-Informed Pelvic Examination Practices Among Clinicians [A286]. (May 2022) - Terrell, Stephanie; Mehari, Kathleen; Oshman, Lauren; Otto, Alana K.; Ruff, Allison; Owens, Lauren
Abstract : INTRODUCTION: Most people have experienced assault, an adverse childhood event, or other trauma. Trauma adversely impacts reproductive health outcomes and patients' experiences of health care. Survivors' preferences for trauma-informed pelvic care are established in the literature, but there are scant data on clinicians' adherence to these practices. This study assessed clinicians' knowledge, attitudes, and practices regarding trauma-informed care (TIC) and pelvic examinations. METHODS: The study team distributed an anonymous Qualtrics survey to 1, 017 clinicians across 12 departments at a large academic medical center in June 2021. Clinicians who had performed at least one pelvic examination in the last year were eligible. Descriptive statistics are reported. RESULTS: Of 1, 017 clinicians contacted, 362 responded, for a response rate of 35.6%. Overall, 81 (22.4%) reported no familiarity with TIC, and 106 (29.3%) had no training in TIC. Although 203 (56.1%) thought it was extremely important to use a trauma-informed approach to the pelvic examination when patients had a known history of trauma, only 88 (24.3%) thought it was extremely important to use a trauma-informed approach when no trauma history was known. Ninety-seven clinicians (26.8%) endorsed using trauma-informed practices during pelvic examinations "often" or "always." CONCLUSION: Clinicians reported a lack of training in TIC. They did not see the need for universal application of TIC, and they reported inconsistent usage of trauma-informed practices during pelvic examinations. These data demonstrate a pressing need to improve training for clinicians and appropriate care for patients.